THE AWAKENING (1899): BREAKING WITH THE PARADIGM - Wolwacz, Andrea Ferras (Organon, 2018)
Kate Chopin is a important writer whose novel The Awakening (1899) written in the end of Victorian Era in the United States broke away from women’s writings of that time. The Novel deals with the condition of nineteenth-century women, a theme totally unpeculiar for that time. For this reason, when Kate Chopin’s novel was published, it provoked reactions in its reviews. Critics censured in the national press and taken from circulation. One of the reasons The Awakening was dropped out of sign was that, for the first time, a female main protagonist, Edna Pontellier, explicitly violates “the modes and codes of nineteenth-century American women`s behavior” KEYWORDS: Kate Chopin; Women’s writing; Solitary novel; Defy values